2014
DOI: 10.1111/1095-9270.12060
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Construction Evidenced by Ship 17 of Thonis-Heracleion

Abstract: Ship 17 is the first of 63 vessels from the submerged city of Thonis‐Heracleion in Egypt to have been excavated. The peculiar constructional features of this ship, which dates to the Late Period (722–332 BC), allow us to argue for a previously undocumented type of construction that finds parallels in Herodotus' description of a Nilotic freighter known as a baris (History, 2.96, c.450 BC). The aim of this article is to outline the main characteristics and the possible sequence of construction of Ship 17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The hull was made of sturdy, short lengths of acacia wood laid in a characteristic ‘courses of bricks’ pattern. Multiple runs of planks were fastened together using very long tenon‐ribs; for example, on the starboard side of the vessel a transversal section revealed that a single 1.99m long tenon passed through 11 strakes (Belov, ; : 197, fig. 10a).…”
Section: Vessel Reusementioning
confidence: 99%
See 1 more Smart Citation
“…The hull was made of sturdy, short lengths of acacia wood laid in a characteristic ‘courses of bricks’ pattern. Multiple runs of planks were fastened together using very long tenon‐ribs; for example, on the starboard side of the vessel a transversal section revealed that a single 1.99m long tenon passed through 11 strakes (Belov, ; : 197, fig. 10a).…”
Section: Vessel Reusementioning
confidence: 99%
“…Richards, : 155–156) and floated into position adjacent to a small island with a jetty on the northern side of the Central Basin. It was then staked into position using 14 long wooden piles, which were driven up to 3m into the clays of the harbour bottom (Belov, : fig. 2, Fig.…”
Section: Vessel Reusementioning
confidence: 99%
“…The excavation of Ship 17 of Thonis‐Heracleion was carried out by the Institut Européen d'Archéologie Sous‐Marine (IEASM) directed by F. Goddio in 2009–2011 (Belov, : 314, fig. 1).…”
Section: Ship 17mentioning
confidence: 99%
“…In the majority of cases, the joint is situated in the lower third of the thickness of the keel but sometimes it can be found in its middle. The tongues are usually slightly trapezoidal in section (Belov, : 317, fig. 6).…”
Section: Ship 17mentioning
confidence: 99%
See 1 more Smart Citation